Dyspepsia and Depression, Anxiety, Stress Scales (DASS) Score - Gontar Alamsyah Siregar; Sahat Halim; Ricky Rivalino Sitepu (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Background: Dyspepsia is a constellation of symptoms referable to the gastroduodenal region of the upper gastrointestinal tract. Emotional disturbances are often associated with dyspepsia and have been proposed as one of the possible causes of dyspepsia. This study was aimed to evaluate the difference between the severity of dyspepsia using porto alegre dyspeptic symptoms questionnaire (PADYQ) and emotional disturbances using depression, anxiety, stress scales (DASS).Method: This study was a cross-sectional analytical study. All the subjects were evaluated using PADYQ and DASS. PADYQ is classified into four categories (no, mild, moderate and severe dyspepsia symptoms). Data was analyzed using Independent t-test and Mann-Whitney test. A p 0.05 was considered as statistically significant.Results: There were 90 subjects that enrolled in this study, consisted of 47 (52.2%) males and 43 (47.8%) females. Thirty three (36.7%) subjects had PADYQ score was 6, while it was ≥ 6 in the other 57 (63.3%) subjects. DASS scores were significantly different in subjects without dyspepsia symptoms compared to subjects with dyspepsia symptoms. There is a difference in DASS scores between subjects with different categories of dyspepsia symptoms (p 0.05). Conclusion: There was a difference in the severity of emotional disturbances among subjects with dyspepsia symptoms and without dyspepsia symptoms. The severity of emotional disturbances parallel with the severity of dyspepsia. Evaluation of emotional disturbances in case of dyspepsia will be helpful in the management of dyspepsia.